The Role of Pastoral Care and Self-Efficacy in Student’s Self-Regulated Learning - Hatmoko, Tomas Lastari; Laka, Laurensius (Bulletin of Counseling and Psychotherapy, 2025)
Education, as a strategic investment in the development of high-quality human resources, was expected to serve as the primary means of fostering students’ self-regulated learning (SRL) abilities. However, various challenges within Indonesia’s educational system had, in fact, hindered the development of SRL among students – an essential foundation for effective learning. This study aimed to examine the influence of pastoral care and self-efficacy on the SRL of students at Frateran Catholic Senior High School, Malang. Employing a quantitative approach, data were collected from a random sample of 140 students. The data collection instruments consisted of questionnaires representing the three scales, each of which had been previously validated. Statistical analysis was conducted using the SPSS program with multiple regression techniques. The results indicated that the correlation coefficient between the independent variables and the dependent variable was 0.722, which was interpreted as strong. Regarding causality, simultaneous regression analysis yielded a Sig.F value of 0.001, which was lower than 0.05, indicating that the regression model could be used to predict students’ SRL. Furthermore, on a partial basis, both pastoral care and self-efficacy were shown to significantly influence students’ SRL (each with a p-value = 0.001). It was therefore concluded that, both simultaneously and partially, all predictor variables had a significant influence on students' SRL, with self-efficacy exerting a greater effect than pastoral care.